Neuroimaging in Fabry disease: current knowledge and future directions - Cocozza, Sirio; Russo, Camilla; Pontillo, Giuseppe; Pisani, Antonio; Brunetti, Arturo (Insights into imaging, 2018)
Fabry disease (FD) is a rare X-linked disorder characterised by abnormal progressive lysosomal deposition of globotriaosylceramide in a large variety of cell types. The central nervous system (CNS) is often involved in FD, with a wide spectrum of manifestations ranging from mild symptoms to more severe courses related to acute cerebrovascular events. In this review we present the current knowledge on brain imaging for this condition, with a comprehensive and critical description of its most common neuroradiological imaging findings. Moreover, we report results from studies that investigated brain physiopathology underlying this disorder by using advanced imaging techniques, suggesting possible future directions to further explore CNS involvement in FD patients. Teaching Points • Conventional neuroradiological findings in FD are aspecific. • White matter hyperintensities represent the more consistent brain imaging feature of FD • Abnormalities of the vasculature wall of posterior circulation are also consistent features. • The pulvinar sign is not reliable as a finding pathognomonic for FD. • Advanced imaging techniques have increased our knowledge about brain involvement in FD.